Effectiveness Of Education Media On Breastfeeding Behavior Among Pregnant Women At Namrole And Leksula Health Centers In Buru Island, Indonesia - Wance, Ujiyati; Masni, Masni; Stang, Stang; moedjiono, Apik indarty; birawida, Agus bintara (Journal of Neonatal Surgery, 2025)
Background: Breast milk offers optimal nutrition for infants, containing antibodies that safeguard against numerous diseases while meeting their energy requirements. Nevertheless, numerous mothers remain uninformed about the advantages of breastfeeding. Objective: This study aims to determine the effectiveness of education media in promoting breastfeeding behavior in pregnant women. Materials and Methods: experimental research using the quasi-experimental method with a non-equivalent control Group Design. Involving 36 pregnant women divided into two groups, the intervention group was given education (Leaflets and Maternal and Child Health Books) and the control group (Maternal and Child Health books). The sampling technique was Simple Random Sampling, with the sample criteria being third-trimester pregnant women. Leaflet feasibility test results were declared very feasible by two material experts and feasible by two media experts. Data were analyzed using Wilcoxon, Mann-Whitney, and Chi-Square tests. Results: This study demonstrated significant differences in mothers' knowledge and attitudes before and after educational interventions using Leaflets and MCH Books in both the intervention group (p=0.000) and the control group (p=0.000). There was no statistically significant difference between the intervention and control groups (p>0.05). The intervention and control groups exhibited a statistically significant difference in breastfeeding practices (p=0.030). Conclusion: The combination of education through leaflets and Maternal and Child Health (MCH) books is equally effective as MCH books alone in enhancing the knowledge and attitudes of pregnant women; however, it demonstrates greater efficacy in promoting breastfeeding practices.